The Image of Summer in the Works of Matnazar Abdulhakim - Mohichehra Rustamova (Peerian Journals Publishing, 2022)
The poet made effective use of the momentary state of the image of summer and added meaning to our perceptions of summer.
Keywords: emotional depth; human understanding; shadow; analytical approach